Thermostability profiling of MHC-bound peptides: a new dimension in immunopeptidomics and aid for immunotherapy design - Emma C. Jappe (Nature Portfolio, 2020)
Thermostability of the peptide-MHC interaction is important for immunogenicity. Here the authors present a mass spectrometry method to measure thermostability among thousands of peptide-MHC complexes in parallel and a trained artificial neural network to predict immunogenenicity of cancer antigens.